The Effect of Reminder Message Tailoring on Cognitive Intervention Adherence. (17th December 2021) - Dieciuc, Michael; Dilanchian, Andrew; Boot, Walter; Zhang, Shenghao
Abstract: To examine the potential impact of tailored messaging on adherence and attitudes toward text message reminders, a pilot study conducted in advance of the APPT randomized controlled trial systematically manipulated the match between text message content and participants' self-reported motivations to participate in a cognitive intervention study. Older adults (n=40) were asked to engage in cognitive training, in the form of gamified neuropsychological tests, 30 minutes a day for 10 consecutive days, and adherence was tracked remotely over time. Critically, each day text message reminders alternated between messages consistent or inconsistent with participants' previously reported motivations for entering the study. This talk presents results, derived from multilevel modeling, that explore the effectiveness of this simple and cost-effective message tailoring approach for facilitating adherence and engendering positive attitudes toward the reminder system, and implications for programs requiring long-term adherence.